Health-care policies during the COVID-19 pandemic in Mexico: A continuous case of heterogeneous, reactive, and unequal response - Daniela Bautista-Reyes; Jimena Werner-Sunderland; Alondra Coral Aragón-Gama; José Roberto Cabral Duran; Karla Daniela Contreras Medina; Manuel Urbina-Fuentes; Elysse Bautista-González (Health Policy Open, 2023)
Background: The pandemic in Mexico underlined pre-existing health-care system inequalities. Within the first six months of the COVID-19 pandemic, 154 health policies across health institutions were found to be uncoordinated and heterogeneous, leading to health inequalities in access and potential health outcomes. Data & methods: Using a rapid qualitative research methodology, data was collected using purposive sampling of institutional policies published for public access on the official websites of the four public health institutions in Mexico from June 16th, 2020 to October 30th, 2021. This policy review used archival analysis to understand the differences in health-care policies during the COVID-19 pandemic in Mexico. These policies were classified under the RREAL framework and as a continuation of our first publication. Results: During this study, categories of public health response and vaccination dominated the policies enacted. The SSA was the main author of publications. There seems to be a more unified policy response. However, health inequalities persist. Conclusions: The Mexican government continued to be reactive to the increase in cases or the arrival of new variants, rather than preventative. Research and development of policies need to work together in soaring cases like COVID-19 to work more effectively against the economic and epidemiological burden of a pandemic. It is suggested that this “vaccination” should be included in the RREAL classification. Other sectors (i.e. the ministry of foreign affairs) should be considered relevant players in the future management of a pandemic.